Wireless Networks Past, Present and Future: A Technical Review - Umang, (International Journal of Computer Sciences and Engineering, 2025)
Wireless Network provides transmission of information over miles of distance without requiring wires, coaxial cables and fibres etc. It focuses on establishment of communication among devices. Such type of communication can be done through Single hop or Multi hop basis. In this attempt, brief introduction of wireless network is presented. In this paper, classification of wireless network is also discussed based on different features and its types. Further, presented work also highlights Mobile Adhoc Networks along with its specialized new concept known as FANETs (Flying Adhoc Networks). In this attempt, design issues for MAC protocol and comparison between MANETs & FANETs is also discussed. This attempt is very much beneficial for beginners of this domain.